Expansão da agricultura orgânica e os desafios enfrentados por produtores brasileiros na produção e exportação de orgânicos - Pintor, Geisiane Michelle Zanquetta de (2020)
Organic agriculture is based on the use of methods of ecological cultivation, alternative to conventional agriculture, in order to preserve the environment. The expansion of the world market for organic products stemmed from concern about environmental degradation and food safety. However, Brazilian organic producers face challenges both in the production process and to access the international organic market. In this context, the aim of this study was to analyze the evolution of organic production and the challenges for the production and export of Brazilian organic products, particularly for the European market. Data from the Brazilian Institute of Geography and Statistics (IBGE), Ministry of Agriculture, Livestock and Supply (MAPA) and Research Institute of Organic Agriculture (FiBL) on the agricultural area, number of establishments and producers, retail sales, per capita consumption and exports were collected to analyze the evolution of organic production. The available data showed the continuous growth of world organic production between 2000 and 2018. The analysis of the world trade in organics was carried out through the Gravitational Model. The estimated gravitational equation used as a dependent variable the world exports of organics. The independent variables were: Gross Domestic Product (GDP) and the population of organic exporting countries, GDP and population of North America and the European Union, in addition to the agricultural area destined for organic production from both exporting countries, North America and the European Union. According to the result of the model, the determinant variables of organic exports were the GDP of exporting countries, as well as GDP, population and organic agricultural area of North America and the European Union. In addition, interviews were also conducted with Brazilian organic family farmers in order to investigate the challenges these producers have encountered in the production and marketing of organic stems. They answered questions related to organic production, the challenges faced, the importance of public policies for the sector, certification and access to the European market. Regarding the difficulties in production, they mentioned factors such as high cost and bureaucracy of certification, lack of differentiated payment for organic product and unavailability of organic inputs. In relation to the challenges for export to the European organic market, they reported problems such as lack of knowledge of the export process, difficulty in obtaining European organic certification, lack of knowledge of European organic legislation and the European market, as well as the scale of production for export. The producers interviewed consider public policies important for the development of organic agriculture in Brazil, but that need to be improved to meet the needs of organic family producers.